Effects of a 25-km trial on psychological, physiological and stroke characteristics of short- and mid-distance swimmers - Invernizzi, P. L.; Limonta, E.; Bosio, A.; Scurati, R.; Veicsteinas, A.; Esposito, F. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: The aim of this paper was to evaluate the effects of a very long distance swimming task on psychological, biomechanical and physiological responses. Eight swimmers (age 21.0 ± 1.2 years; stature 1.80 ± 0.07 m; body mass 76.7 ± 11.0 kg; means ± SD) participated in a 25-km trial in a swimming pool.